STUDIES OF THE BALKAN OTHERNESS TWO DECADES LATER: HISTORICAL, POLITICAL AND METHODOLOGICAL CHALLENGES OF A PARADIGM - Lazarević Radak, Sanja (Political Review, 2026)
By the end of 20th Century a paradigm based on the assumption of discursive colonization of the Balkans, became a means for scientific understanding of reproduction of stereotypes and alteration of the Balkans in relation to Europe. Becoming a fashionable scientific tool for understanding political, economic and social crises in the Balkans, this paradigm included imagological interpretations of ethnic stereotypes, relatively complex analysis of various representations in travelogues, postcolonial critic and spatial and symbolic geographies. Drawing on some of the results of these studies and pointing out their weak points, the author states the main reasons for loss of relevance of imagological, postcolonial, geographical and other studies, that refer to the Balkans as symbolic geography, and textualy colonized part of the wold. Studies of the Balkan Otherness in Serbia and in academic circles of the Western Balkan region has come a long way from discourse analysis to displacement of criticism to geographical space. The enthusiasm that promised the concrete answers and practical solutions to the consequences of peripheral position of the Balkans, faced pessimistic image of post-transition reality. Less and less popular studies of the Balkans brought impossibility to develop and improve healthy and fertile parts of this scientific frame. In political and identity context, this ambiguity paradoxically proved the subaltern position of the region. The lack of new inspiration and and popularization of 19th century representations and Balkanist phrases led to impossibility of researchers to recognize contemporary material that undoubtedly located the Balkans in postcolonial frame.